Preferentially Expressed Antigen in Melanoma (PRAME) Staining on Eyelid Skin: Comparison with SOX-10 Immunohistochemistry to Establish a Normal Baseline for Evaluating Periocular Melanoma Specimens - Warne, BS*, Melissa M; Meeker, MD, Austin; Lin, MD, PhD, Lin (North American Journal of Medicine and Science, 2022)
The management of periocular melanoma is fraught with difficulty because of the desire to conserve tissue while at the same time ensuring complete removal of neoplastic cells. Chronically sun damaged skin of the face and eyelids is associated with melanocytic hyperplasia that can complicate the histologic interpretation of clear margins. The SRY-Box Transcription Factor 10 (SOX-10) gene is relatively specific for melanocytes within the epidermis but does not differentiate between benign and malignant melanocytes. Preferentially expressed antigen in melanoma (PRAME) is a relatively new marker that may be useful in differentiating benign from malignant melanocytic proliferations. Our aim was to determine baseline staining for PRAME compared to SOX-10 on eyelid skin that does not contain melanoma or junctional melanocytic proliferation to guide margin assessment. We performed a retrospective review of histopathologic specimens of the eyelid. The most recent fifty specimens that did not include a diagnosis of melanoma or a junctional melanocytic proliferation with ≥ 1 mm of normal epidermis were included (n = 50). The first 1 mm of epidermis with a relatively flat surface from the left margin of the skin sample was assessed, and the mean number of cells in the 1 mm window that stained positive for PRAME and SOX-10 was counted. There were on average 28.06 more SOX-10-stained cells than PRAME-stained cells (95% CI 24.83 - 31.29, p < 0.0001). Although SOX-10 staining intensity varied considerably in normal eyelid tissue, PRAME staining was minimal and did not exceed 3 cells and may be more likely with increased age. When PRAME staining is sustained at a rate higher than 3/mm, melanoma in situ should be considered and additional analysis may be warranted. Expression of PRAME detected by immunohistochemical staining can aid in the diagnosis of melanoma arising in a precursor nevus, primary acquired melanosis of the conjunctiva, and conjunctival melanoma. [N A J Med Sci. 2022;15(1):008-012. DOI: 10.7156/najms.2022.1501008] Key Words: Melanoma in situ; lentigo maligna; immunohistochemistry; eyelid; Preferentially expressed Antigen in Melanoma (PRAME); margin; excision; SOX-10; junctional melanocytic proliferation; melanocyte; immunohistochemistry